The Use of Strategic Marketing Tools for Territories to Develop the Domestic Tourism Resource Potential (Economics and region, 2020)
The aim of the article is to research of the features and to develop a set of recommendations for the use of strategic marketing tools for territories to develop the resource potential in Ukraine. The use of tourism resource potential is played an important role in the domestic tourism development. It is shown that the domestic tourism resource potential development is determined by the tourist product, the tourist infrastructure, the territory promotion, and the destination brand. The use of strategic marketing innovative tools and marketing support is grounded. The components of strategic marketing of territories are determined. The use of "portfolio" strategy in territorial marketing is proposed. The general tools of territorial marketing are given. It is substantiated that the Kharkiv region has a significant resource potential for the domestic tourism development. To form a positive image of Kharkiv as a tourist destination the implementation of an image marketing strategy is proposed. The competitive advantages of Kharkiv as an attractive tourist destination, a perspective center of exhibition and congress activities are determined.
Keywords: strategic marketing; resource potential; territorial marketing; destination branding; domestic tourism; region